A 15-Year Follow-up Retrospective Study on 959 Spine Surgeries: What Can We Learn From Real-world Data?. Issue 5 (June 2021) - Plazier, Mark; Raymaekers, Vincent; Bruyneel, Luk; Coeckelberghs, Ellen; Sermeus, Walter; Vanhaecht, Kris; Duyvendak, Wim
Abstract : Study Design: This was a retrospective study. Objective: The aim of this study was to investigate the patient flow and need for additional surgery after first-time lower back surgery. Next, we analyzed the patients who developed chronic low back pain (LBP) and were treated with spinal cord stimulation. Summary of Background Data: LBP has a lifetime prevalence of 84% and imposes a high economic burden. Treatment is focused on preventing chronic pain. Research has shown the efficacy of treatment options. However, less is known about who benefits the most from which therapy and when they should be positioned in the treatment algorithm. Methods: In this retrospective study, data of all patients who underwent first-time surgery from 2000 to 2004 were included. After 10–15 years, patients were contacted about their quality of life (QoL) (EuroQoL-5 Dimension) and life and heath perception (EuroQoL Visual Analogue Scale). Results: In all, 959 patients underwent surgery at the lower back area. Follow-up time ranged from 13 to 17 years; 225 patients (23.5%) underwent a second surgery. In total, 20 patients (2.1%) developed chronic neuropathic back pain and received spinal cord stimulation therapy. Ten years postsurgery, 438 (45.7%) patients completed the QoL and LBP questionnaires. The health-related QoL and health situation were significantly lower in patients with multiple surgeries ( P <0.001). Conclusions: The study results indicate that large data sets, with multiple outcome measurements and long-term follow-up are necessary to improve our knowledge and to optimize the therapeutic pathway. In that way, we might learn how to select a patient for the right treatment or treatments at the right moment and shorten the circulation in our health care system. Abstract : Supplemental Digital Content is available in the text.